FAKTOR-FAKTOR HUBUNGAN KEJADIAN HIPERTENSI PADA IBU HAMIL TRIMESTER II DI WILAYAH KERJA PUSKESMAS LEMPUR KABUPATEN KERINCI - Tyas, Dina Ayuning; Suganda, Yohana; Silvia, Elwitri; Nengsih, Novelia (Ensiklopedia of Journal, 2025)
Abstract: Hypertension disorders in pregnancy (hypertension pregnancy disorders) are a cause of increased maternal, fetal and neonatal morbidity and mortality. Pregnant women with hypertension are at high risk for serious complications such as placental abruption, cerebrovascular disease, organ failure and intravascular coagulation. The aim of this research is to determine the factors relating to the incidence of hypertension in pregnant women in the work area of the Lempur Community Health Center, Kerinci Regency in 2024. This type of research uses descriptive analytical methods with a cross sectional approach. The population in this study was 52 people, a sample of 32 people and the sampling technique used purposive sampling technique. Data were collected using a questionnaire, and data analysis included univariate analysis and bivariate analysis with the chi-square test. Of the 32 respondents, it was found that the incidence of hypertension was 22 respondents (68.8%), > 35 years, namely 18 respondents (56.8%), risk parity was 23 respondents (71.9%), obesity was 22 respondents (68.8%), 22 respondents (68.6%) were stressed. Conclusions from this research: There is a relationship between age p- value = 0.008 (p<0.05), There is a relationship between parity pvalue = 0.000 (p<0.05), There is a relationship between obesity p-value = 0.027 (p<0.05 ), There is a stress relationship p-value = 0.003 (p<0.05). the incidence of hypertension in pregnant women. So there are several factors that greatly influence the incidence of hypertension in pregnant women, namely age, poverty and stress in the Lempur health center work area. Keywords: hypertension, age, parity, obesity, stress.